2012
DOI: 10.1074/jbc.m111.312702
|View full text |Cite
|
Sign up to set email alerts
|

A Myeloid Hypoxia-inducible Factor 1α-Krüppel-like Factor 2 Pathway Regulates Gram-positive Endotoxin-mediated Sepsis

Abstract: Background: Gram-positive bacterial infections and sepsis are a significant cause of morbidity and mortality. Results: KLF2 inhibits Gram-positive, bacterial endotoxin-induced HIF-1␣ expression and macrophage activation. Conclusion: Transcription factors KLF2 and HIF-1␣ are critical regulator of Gram-positive sepsis. Significance: Pharmacological agents that modulate the KLF2/HIF-1 pathway may allow for therapeutic gain in the treatment of bacterial infections and sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 33 publications
3
40
0
Order By: Relevance
“…However, Kruppel-like factor 2 (KLF2) could be considered a potential candidate in light of recent reports revealing its role in PHD-independent HIF-1␣ proteasomal degradation, through direct disruption of the HSP90/HIF-1␣ complex (22). In addition, signaling pathways of KLF2 and HIF-1 have been recently shown to be interconnected upon bacterial infection (30,31). A second consideration could be direct interference with the ubiquitination stage of protein degradation, as evidence has already revealed that microbial compounds could target this pathway (45).…”
Section: Discussionmentioning
confidence: 99%
“…However, Kruppel-like factor 2 (KLF2) could be considered a potential candidate in light of recent reports revealing its role in PHD-independent HIF-1␣ proteasomal degradation, through direct disruption of the HSP90/HIF-1␣ complex (22). In addition, signaling pathways of KLF2 and HIF-1 have been recently shown to be interconnected upon bacterial infection (30,31). A second consideration could be direct interference with the ubiquitination stage of protein degradation, as evidence has already revealed that microbial compounds could target this pathway (45).…”
Section: Discussionmentioning
confidence: 99%
“…When mice with conditional Hif1a deletion in the myeloid lineage are challenged with LPS, they exhibit reduced hypothermia and hypotension, along with enhanced survival compared with mice that express myeloid HIF-1α (39). Myeloid HIF-1α deficiency is also protective in a gram-positive endotoxin-induced murine sepsis model (144). Similar to HIF-1α, deletion of myeloid HIF-2α is also protective against sepsis.…”
Section: Hifs In Myeloid Cellsmentioning
confidence: 99%
“…51 However, in the face of Gram-positive and Gram-negative septicemia, HIF-1α-deficiency confers protection attributable to attenuation of myeloid cell activation and systemic cytokine release. 52 In contrast to HIF-1α, HIF-2α limits nitric oxide production by induction of Arg1, an enzyme competing for l-arginine substrate availability. Via Arg1, HIF-2α induces ornithine and polyamine or urea production.…”
Section: Hypoxia Inducible Factorsmentioning
confidence: 99%